2018
DOI: 10.1007/s11011-018-0311-6
|View full text |Cite
|
Sign up to set email alerts
|

Leptin stimulates the release of pro-inflammatory cytokines in hypothalamic astrocyte cultures from adult and aged rats

Abstract: Leptin is an adipose tissue-derived hormone that acts on the hypothalamus in order to maintain energy homeostasis. However, leptin can also induce an inflammatory response. Increasing evidence has highlighted a critical role of astrocytes in the effects of leptin on the hypothalamus. In addition, astrocytes participate in neuroinflammation by producing and releasing a wide range of inflammatory mediators. In this study, we aimed to investigate the age-dependent effect of leptin on pro- and anti-inflammatory cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Astrocytes and oligodendrocytes actively modulate the chemical environment of all brain cells. Thus, astrocytes release ATP [19][20][21] (to mediate Ca 2+ -signaling among glial cells [22] and in response to sleep-pressure [23]), glutamate to control synaptic strength [24] and several cytokines and chemokines [25][26][27]. Glial dysfunction is responsible for a wide spectrum of neurological diseases (e.g., [28][29][30][31]).…”
Section: Introductionmentioning
confidence: 99%
“…Astrocytes and oligodendrocytes actively modulate the chemical environment of all brain cells. Thus, astrocytes release ATP [19][20][21] (to mediate Ca 2+ -signaling among glial cells [22] and in response to sleep-pressure [23]), glutamate to control synaptic strength [24] and several cytokines and chemokines [25][26][27]. Glial dysfunction is responsible for a wide spectrum of neurological diseases (e.g., [28][29][30][31]).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies and our study both observe that OVX mice, an experimental mouse model for menopause, displayed visceral obesity showing increased body weight and adiposity [ 29 ]. Moreover, numerous studies have reported that sustained elevation of substances derived from visceral fats triggers hypothalamic inflammation concomitant with reactive gliosis [ 30 , 31 ]. In agreement with this, we successfully confirmed that OVX mice showed elevated hypothalamic inflammation by analyzing the expression of genes involved in cellular inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Well-known instances for the toxicity resulting from misfolded and unfolded proteins are accumulations of amyloid fibrils and tau proteins in Alzheimer's disease, huntingtin protein in Huntington disease, and α synuclein protein in Parkinson's disease (Martínez et al, 2017;Selkoe, 2003). Creative interventions, which include physical exercise and lowering insulin levels via CR, have been observed to be among some of the efficient approaches to reverse the detrimental processes following increase in ER-stress (Bergamini et al, 2004;Estébanez et al, 2018), and this is in addition to their anti-oxidant and anti-inflammatory properties (Caracciolo et al, 2014;Csiszar et al, 2009;Mohammadi et al, 2014;Santos et al, 2018;Speakman and Mitchell, 2011;Tucsek et al, 2013). One of the mechanisms proposed related to CR-mediated anti-inflammatory effects comes from upregulating nuclear factor-erythroid-2-related factor 2 (Nrf2)-dependent cytoprotective mechanisms that confers protection of the genetic material inside cells as well as integrity of the blood brain barrier (BBB) (Ungvari et al, 2019).…”
Section: Cr and Altered Intercellular Communicationmentioning
confidence: 99%